Plastic Waste in Latin America and the Caribbean (LAC): Impact on the Environment and Public Health—A Systematic Review - Danladi Chiroma Husaini; Rodeli Kaylin Mendez; Michael Arzu; Lydia Harris-Thurton (Journal of Toxicology)
Background. The global spread and accumulation of plastics in freshwater, marine, and terrestrial settings are of great concern to public health and the environment, especially in developing countries with few resources. In the Caribbean and Latin America, nearly 17,000 tons of plastic waste are generated and trashed daily in open dumpsites with attendant consequences for the environment, the economy, aquatic life, the beauty of sea beaches, and public health. The increased use of plastics threatens public health and the ecosystem. Main Body. This systematic review assessed the impact of plastic waste on the environment, economy, and public health in LAC by searching relevant databases such as PubMed, HINARI, Google Scholar, and Scopus. PRISMA and Rayyan software were used to select and analyze research articles for the review. Conclusions. The review showed that plastic pollution significantly impacts the environment, aquatic life, economy, and human health in LAC. The review further indicated that countries in LAC are working assiduously to address the issues associated with plastic pollution. The use of biodegradable plastics, cleanup campaigns, and policies/programs to reduce or ban plastics are some current efforts in many LAC countries. More research on the impact of plastic waste needs to be conducted, especially in the Caribbean, to address and mitigate the challenges of plastic pollution.